Design of Smart Key Box Using IoT - Thanat Nonthaputha; Usa Torteanchai; Montree Kumngern; Jirapat Phookwantong (My University, 2021)
This paper presents a design of smart key box using internet of things (IoT). It has been designed to be kept 8 keys that has been used in case of laboratory key-borrowing and returning for students. They can take the keys by themselves that use identity card which have been registered in database. It can save an important database with names, surnames, level of users and times. The administrator can access the database by logging-in password. It is convenient that the students can borrow and return a key by themselves. A several data from the database will be sent to the administrator’s smart phone via messages in Line application. Moreover, it has a sound from the speaker to guide every steps when it is operated.
Keywords: IoT-based Smart Home Systems